2002
DOI: 10.1038/sj.onc.1206010
|View full text |Cite|
|
Sign up to set email alerts
|

MyoD induces apoptosis in the absence of RB function through a p21WAF1-dependent re-localization of cyclin/cdk complexes to the nucleus

Abstract: During differentiation of skeletal myoblasts, MyoD promotes growth arrest through the induction of the cdk inhibitor p21 and the accumulation of hypophosphorylated RB protein. Myoblasts lacking RB function fail to accomplish full differentiation and undergo apoptosis. Here we show that exogenous MyoD induces apoptosis in several cell backgrounds sharing RB inactivation. This process is associated with increased levels of cell cycle-driving proteins and aberrant cell cycle progression. The inability of MyoD to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 66 publications
3
31
0
Order By: Relevance
“…The survival effect of P21 waf1/cip1 has been reported to be linked to cytoplasmic localization (Asada et al, 1999;Coqueret, 2003), whereas the apoptotic effect of P21 waf1/cip1 would occur when P21 waf1/cip1 is present in the nucleus (Ritt et al, 2000;Peschiaroli et al, 2002). In accordance with these reports, we showed that NaB-induced apoptosis was associated with an increase of P21 waf1/cip1 , particularly in the nucleus.…”
Section: Discussionsupporting
confidence: 81%
“…The survival effect of P21 waf1/cip1 has been reported to be linked to cytoplasmic localization (Asada et al, 1999;Coqueret, 2003), whereas the apoptotic effect of P21 waf1/cip1 would occur when P21 waf1/cip1 is present in the nucleus (Ritt et al, 2000;Peschiaroli et al, 2002). In accordance with these reports, we showed that NaB-induced apoptosis was associated with an increase of P21 waf1/cip1 , particularly in the nucleus.…”
Section: Discussionsupporting
confidence: 81%
“…It was thus unexpected to find a high level of p21 together with a large pool of hyper-ppRb in clones expressing R453W-lamin A. This apparent discrepancy may be explained by the dual role of p21, which, besides its function as a cdk inhibitor, can induce nuclear accumulation and aberrant activity of cyclin-cdk complexes in the presence of MyoD and in the absence of functional pRb, resulting in increased apoptosis frequency (44).…”
Section: Vol 24 2004 Mutation In Lamin a Inhibits In Vitro Myogenesmentioning
confidence: 97%
“…Terminal muscular differentiation is a stepwise process. At an early stage, MyoD directly upregulates pRb, p21, cyclin D3, and myogenin expression in a Rb-independent manner (1,7,39,44). Subsequently, activation of late differentiation genes in normal cells is induced by both myogenin and MyoD.…”
Section: Vol 24 2004 Mutation In Lamin a Inhibits In Vitro Myogenesmentioning
confidence: 99%
“…The role of p21 Cip1 in lymphocytes is less clear. Various reports suggest that p21 Cip1 may act to inhibit apoptosis (8), promote cell cycle withdrawal upon prolonged stimulation (9), or promote apoptosis (10). More recent data suggest that p21 Cip1 plays a role in Fas-mediated activation-induced cell death (11,12).…”
mentioning
confidence: 99%